RETRACTED ARTICLE: LncRNA TUG1 was upregulated in osteoporosis and regulates the proliferation and apoptosis of osteoclasts - Ye Han; Chunying Liu; Ming Lei; Shaosong Sun; Wenkui Zheng; Yanan Niu; Xi Xia (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background Long non-coding RNA (LncRNA) TUG1 plays critical roles in the development of human cancers. Its inhibition has been proved to participate in ankylosing spondylitis, which is an inverse pathological procedure of osteoporosis. In the present study, we aim to investigate the role of lncRNA TUG1 in ankylosing spondylitis. Materials and methods Expressions of lncRNA TUG1 in plasma of 98 patients with osteoporosis and 60 healthy participants were detected by real-time quantitative PCR (RT-qPCR). Diagnostic values of lncRNA CASC11 for osteoclasts were performed by the ROC curve with osteoporosis patients as positive and healthy participants as negative. All experiments were repeated 3 times. Mean ± standard deviation was calculated. Results We found that plasma lncRNA TUG1 was upregulated in osteoporosis patients than in healthy participants. Upregulation of plasma lncRNA TUG1 distinguished osteoporosis patients from healthy participants. LncRNA TUG1 level increased with the advances of clinical stages. Over-expression of lncRNA TUG1 promoted the proliferation and inhibited the apoptosis of mice osteoclasts, while lncRNA TUG1 siRNA silencing played an opposite role. In addition, lncRNA TUG1 over-expression led to downregulated PTEN, while lncRNA TUG1 siRNA silencing played an opposite role. Conclusion Therefore, lncRNA TUG1 is upregulated in osteoporosis and regulates the proliferation and apoptosis of osteoclasts. lncRNA TUG1 knockdown may serve as a promising therapeutic target for osteoporosis by inhibiting the proliferation and promoting the apoptosis of osteoclasts through PTEN.